Menjembatani Kesenjangan Digital dalam Akses JKN: Fasilitasi Literasi Kesehatan Layanan PANDAWA BPJS Kesehatan di Tingkat Pelayanan Primer: Bridging the Digital Gap in JKN Access: Facilitating Health Literacy of BPJS Kesehatan's PANDAWA Services at the Primary Care Level - Rofi’atun Zakiah; Harto Waldi Tamara; Hifni Mudhoffar Nu’man; Melia Haryanti; Antik Argiyanti (Jurnal Pengabdian Masyarakat Saga Komunitas, 2025)
Background: Technological advancements have accelerated digital transformation in public services, including the introduction of PANDAWA by BPJS Kesehatan. However, disparities in digital health literacy among community members remain a major barrier to optimizing access to administrative services under Indonesia’s National Health Insurance (JKN) program. This community engagement initiative aimed to improve participants’ health literacy, procedural understanding, and independence in accessing and utilizing PANDAWA services. Methods: The program was conducted in the service area of UPTD Puskesmas Tapos on November 13, 2025, involving 30 participants through a participatory approach that integrated lectures, feature demonstrations, hands-on practice using official leaflets, and facilitated interactive discussions. Program outcomes were quantitatively evaluated using a pre-test and post-test design Results: The results demonstrated a substantial increase in the proportion of participants with high health literacy, from 43% at pre-test to 80% following the intervention. Improvements in practical skills included participants’ ability to independently access PANDAWA through its designated single contact number and understand eight types of digital administrative services without requiring an in-person visit to a BPJS Kesehatan branch office. Conclusion: The program achieved its objectives of strengthening digital health literacy and promoting community independence in accessing PANDAWA services. These findings suggest that the intervention has the potential to support more efficient, cost-effective, and inclusive access to JKN administrative services at the primary healthcare level.